2019
DOI: 10.1039/c8np00092a
|View full text |Cite
|
Sign up to set email alerts
|

Marine natural products

Abstract: A comprehensive review of 1490 new MNPs including the first naturally occurring blue zwitterionic quinoids dactylocyanines A–H is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
356
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(378 citation statements)
references
References 721 publications
(522 reference statements)
3
356
0
1
Order By: Relevance
“…Marine natural products, comprising a huge variety of chemical structures and being a serendipitous source of new molecules, could play a key role on this need [26][27][28][29][30][31]. In fact, the biomedical and pharmacological potential of marine natural products is known to be still underexplored [32,33]. In a previous study of our group, aimed to find possible molecular targets for a set of marine natural products, we observed that some of them can interact with proteins involved in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Marine natural products, comprising a huge variety of chemical structures and being a serendipitous source of new molecules, could play a key role on this need [26][27][28][29][30][31]. In fact, the biomedical and pharmacological potential of marine natural products is known to be still underexplored [32,33]. In a previous study of our group, aimed to find possible molecular targets for a set of marine natural products, we observed that some of them can interact with proteins involved in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Marine fungi are a relevant and active component of the microbial communities that inhabit the oceans [1]. Fungi in the marine environment live as mutualists, parasites, pathogens and saprobes, and are pivotal to marine food webs because of the recycling of recalcitrant substrata [2]; besides, these widely dispersed organisms are a source of novel bioactive compounds [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is a trend in the field of marine natural products to associate antifouling activity with cytotoxicity, a theory which is reinforced by the fact that a large number of marine secondary metabolites, which crafted by nature to provide marine organisms with chemical weapons to face ecological challenges such as biofouling, also show cytotoxic activity. [28] However, the reverse argument that cytotoxic terrestrial natural products may also display antifouling activity in the marine environment is not necessarily true. This is evidenced by the results of the present work, in which olivacine (1), a compound of known cytotoxic activity, [29] was a very poor antifoulant.…”
Section: Resultsmentioning
confidence: 99%